Analysis of financing resources management of yogyakarta islamic elementary school (SD) - Qiyadah Robbaniyah; Roidah Lina; Pricillia Anggita Sari; Novia Indah Nur Agni (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2022)
Abstract: Good management of financing resources is one of the keys to the success of the institution so that all elements of the school can run and develop. Islamic Elementary Schools that are accredited and have good management of funding resources include SD BIAS, SD Muhammadiyah Condong Catur, SD Ungulan Aisyiyah. Seeing this urgency, researchers want to analyze 3 Islamic SDs in Yogyakarta so that they can become references for other institutions. The research method used is qualitative by collecting interview data and documentation. The data analysis used is firstly describing the data obtained in the field, secondly entering into sub-sections, thirdly analyzing the results of the data obtained. From the results of the study it was found that the Analysis of Management of financing facilities at SD Islam Yogyakarta, namely SD BIAS, SD Muhammadiyah Condong Catur, SD Unggulan Aisyiyah Bantul, namely: 1) Internal income, first: School Cooperative Second: Cathering lunch and snacks 2) External income, obtained from Registration Money, Entrance Fee. Development costs, development costs, uniform fees and student books, regional boss funds, national boss funds, infaq student guardians, assistance from students' guardians, funding from foundations. 3) Planning and Management, Management in terms of costs starts with the formation of a structure, namely those responsible for financial management and operational management who have duties and authority in planning, monitoring, evaluating and managing finances in the institution. Making RKT and RKAS which are planned before the start of a new teaching and agreed upon by all teachers and approved by the head of the foundation. The RKT and RKAS include daily, monthly, semi-annual and annual operations as well as development. Reporting and monitoring of finances is carried out in a transparent manner with regular meetings once a month. 4) Evaluation, in implementing the budget needs and requests from schools all must be adjusted from the RKT and RKAS that were planned at the beginning of the year. At the end of each year or at the beginning of the year an internal audit and an external audit are carried out